All-inorganic perovskite solar cells featuring mixed group IVA cations. Issue 16 (5th April 2023) - Li, Yufeng; Yang, Changyu; Guo, Weisi; Duan, Tianwei; Zhou, Zhongmin; Zhou, Yuanyuan
Abstract : The fundamental structures and solar-cell performance of all-inorganic ABX3 perovskites that contain mixed group IVA cations at the B sites are examined comprehensively, pointing to an interesting direction in exploring perovskites with reduced Pb inclusion. Abstract : All-inorganic perovskites are promising for solar cells owing to their potentially superior tolerance to environmental factors, as compared with their hybrid organic–inorganic counterparts. Over the past few years, all-inorganic perovskite solar cells (PSCs) have seen a dramatic improvement in certified power conversion efficiencies (PCEs), demonstrating their great potential for practical applications. Pb, Sn, and Ge are the most studied group IVA elements for perovskites. These group IVA cations share the same number of valence electrons and similarly exhibit the beneficial antibonding properties of lone-pair electrons when incorporated in the perovskite structure. Meanwhile, mixing these cations in all-inorganic perovskites provides opportunities for stabilizing the photoactive phase and tailoring the bandgap structure. In this mini-review, we analyze the structural and bandgap design principles for all-inorganic perovskites featuring mixed group IVA cations, discuss the updated progress in the corresponding PSCs, and finally provide perspectives on future research efforts faciliating the continued development of high-performance Pb-less and Pb-free all-inorganic PSCs.